EARLY RHEUMATOİD ARTHRİTİS - Ali Aydeniz,; Faruk Şendur,; Gülcan Gürer, (Archives of Rheumatology, 2005)
Rheumatoid arthritis is a disease that leads to joint damage and loss of function. Recent studies have shown that irreversible damage ocur within the first two years of the disease. For this reason there is a consensus about early diagnosis and proper treatment of the disease. In this review new improvement in diagnosis and treatment of rheumatoid arthritis is reviewed.